Relative exon affinities and suboptimal splice site signals lead to non-equivalence of two cassette exons. - Andreadis, A (1995)
Tau is a microtubule-associated protein whose transcript undergoes complex regulated splicing in the mammalian nervous system. Exons 2 and 3 of the gene are alternatively spliced cassettes in which exon 3 never appears independently of exon 2. Expression of tau minigene constructs in cells indicate that exon 2 resembles a constitutive exon, while a suboptimal branch point connected to exon 3 inhibits inclusion of exon 3 in the mRNA. Splicing of the two tau exons is controlled by their relative affinities for each other versus the affinities of their flanking exons for them.